Pengembangan Website Kamus Logistik Untuk Meningkatkan Efisiensi, Kualitas dan Komunikasi di Dalam Industri Logistik - Putri, Dhiyananda Haniifah; Baihaki, Muhammad Viki; Sahara, Siti (Jurnal Ilmiah Global Education, 2024)
In the current digital era, efficiency, quality and communication are the main keys to the logistics sector. This review discusses the development of a logistics dictionary website as a solution to improve these three aspects. The Logistics Dictionary website is designed to facilitate the exchange of information between various parties in the logistics industry, including shippers, recipients and logistics service providers. By integrating various data and information related to logistics, this website aims to increase operational efficiency, improve service quality and improve communication between stakeholders. The development of this website involved analyzing user needs and preferences, as well as developing an intuitive and easy-to-use user interface. Apart from that, this website is also equipped with features such as fast search, filters to help users easily search for and choose logistics services that suit their needs. This journal shows that developing a logistics dictionary website can have a significant positive impact on the logistics sector, by increasing operational efficiency, improving service quality and improving communication between parties. The results of this research provide valuable insight into how information technology can be used to improve efficiency and quality in the logistics sector.